PEMBUATAN ARANG KAYU KARET (Hevea brasilliensis) PADA TUNGKU KUBAH MODEL S-93 - Tjutju Nurhayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Dome kiln of S-93 model with 1.40 m3 capacity was built for charcoal production of rubber wood (Hevea brasilliensis). Two clones of rubber wood used as raw materials were AVROS 2037 and GT-Twhich were 15 and 25 years old, respectively.Charcoal yield, conversion efficiency from wood 10 charcoal, rate of production and quality between AVROS and GT-T were not significant. the percentage of yield was 26.9 % , efficiency was 39.2 % and rate of production was 1.6 kg/hour. the quality of charcoal showed that volatile melter content was 17.43 %, fixed carbon 78.64 %, ash content 3.92 % and catoriffic value 6582 kcal/kg.